Examining the Specificity of Smartphone ECG Devices in Decision-Making for ST-Elevation Myocardial Infarction and Non-ST-Elevation Myocardial Infarction - mahajan, Sahil; Garg, Salil; Singh, Yogendra; sharma, richa; Bhatia, Tanuj; chandola, nitin; agarwal, deeksha (Jurnal Kardiologi Indonesia, 2024)
Background & Objectives: Electrocardiography (ECG) stands as a cornerstone diagnostic tool for assessing cardiac health, particularly in ruling out abnormalities. The integration of smartphone devices presents a promising avenue for expedited detection of cardiac irregularities. This study aims to evaluate the diagnostic efficacy of smartphone ECG devices in subjects admitted to Cardiac Care Units (CCUs) and Cardiac Intensive Care Units (CICUs). Methods: A retrospective analysis was conducted on a cohort comprising 62 patients presenting with cardiac symptoms. Utilizing smartphone ECG devices as the index, 12-lead ECG tests were administered alongside the Gold Standard ECG machine for comparison among patients in CCUs and CICUs. Diagnostic decisions concerning the presence of ST-Elevation Myocardial Infarction (STEMI) or Non-ST-Elevation Myocardial Infarction (NSTEMI) were made by a team of cardiologists following a meticulous review of both sets of ECG reports. Results: Data analysis was conducted on 56 patients. The smartphone-based ECG device exhibited 100% specificity, 93% sensitivity, 80% Negative Predictive Value, and 100% Positive Predictive Value, yielding an F-score of 0.96 and a Mathew Correlation Coefficient value of 0.86. Discussions: This study unequivocally underscores the significant potential of the Spandan ECG device in accurately identifying a range of cardiac abnormalities, including critical conditions such as STEMI and ischemia. Despite its portable nature, smartphone ECG technology demonstrates utility within Critical Care Units for timely monitoring and diagnosis.